CPW FED dual band antenna for IOT application - Das S K, Vyshnavi; Shanmuganantham, T (International Journal of Engineering and Technology, 2018)
This work proposes a Coplanar Wave Guide (CPW) fed dual band antenna for Internet of Things (IoT) application. The substrate of the antenna is selected to be FR4 of dielectric constant 4.4 and loss tangent 0.02. The operating bands of the antenna are (4.17-5.06) GHz and (5.28-6) GHz with impedance bandwidth of 890 MHz and 720 MHz respectively. The simulated gain and efficiency of the antenna at 4.72 GHz and 5.73 GHz are 1.8 dBi, 83% and 2.5 dBi and 90% respectively. The operating frequency bands of antenna found to be in the WiFi range with the prerequisites of IoT application.
Keywords: Coplanar Wave Guide (CPW); Dielectric Constant; Dual Ban; Internet of Things (IOT); Loss Tangent.